1978
DOI: 10.1002/1097-0142(197810)42:4<1730::aid-cncr2820420411>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intensification and maintenance programs in the treatment of acute lymphoblastic leukemia

Abstract: This cooperative prospective study was designed to answer the following questions in cases with acute lymphoblastic leukemia induced to achieve complete remission with the combination of vincristine and prednisone (if by day 29 the bone marrow was not M1, daunorubicin was added to the former regimen) and who received preventive CNS therapy with 2400 rad of cobalt-60 to craniocervical region and simultaneously intrathecal methotrexate and dexamethasone: 1) Is a short intensification with cytosine-arabinoside an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The explanation for the effect of low‐dose maintenance therapy must remain speculative at this point. However, prolonged exposure to low‐dose chemotherapy is well established as a crucial element of therapy of ALL, for example 17, and anti‐angiogenetic effects have been suggested to occur after prolonged exposure to low‐dose chemotherapy 18. Furthermore, a number of drugs are known to target different cellular and molecular mechanisms at different dosages.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for the effect of low‐dose maintenance therapy must remain speculative at this point. However, prolonged exposure to low‐dose chemotherapy is well established as a crucial element of therapy of ALL, for example 17, and anti‐angiogenetic effects have been suggested to occur after prolonged exposure to low‐dose chemotherapy 18. Furthermore, a number of drugs are known to target different cellular and molecular mechanisms at different dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Argentina has been providing public support to care for children and adolescents with cancer regardless the insurance status since treatment for childhood cancer became available in the 1970s. 11 There is a National Cancer Institute (NCI) that sets policy, but is not involved in direct patient care. The NCI launched an NPCCP and a National Cancer Registry and is leading an effort to stratify treatment units across the country.…”
Section: Argentinamentioning
confidence: 99%
“…A clinical trial of levamisole in advanced human breast cancer showed a significant prolongation of the provements .3,5+ 1920* [25][26][27] 0008-543X/81/1000/1500 $0.90 0 American Cancer Society…”
mentioning
confidence: 99%